Peran Mahkamah Agung dalam Penyelesaian Sengketa Administrasi Negara - Selma Kemuning Aquinta (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the role of the Supreme Court in resolving state administrative disputes in Indonesia. As the pinnacle of judicial power, the Supreme Court has judicial, supervisory, and regulatory authority to uphold law and justice. The study employed a normative juridical method with a prescriptive approach. The results indicate that the Supreme Court's role faces various obstacles, including a high caseload, limited number of judges, overlapping authority, and a low understanding of administrative law. Reform through digitalization, increased capacity of judges, and simplified procedures are needed to strengthen legal protection for the public.